Oxidative and nitrosative stress pathways in the brain of socially isolated adult male rats demonstrating depressive- and anxiety-like symptoms - Filipović, Dragana; Gass, Peter (Brain structure & function, 2017)
Various stressors may disrupt the redox homeostasis of an organism by causing oxidative and nitrosative stress that may activate stressor-specific pathways and provoke specific responses. Chronic social isolation (CSIS) represents a mild chronic stress that evokes a variety of neurobehavioral changes in rats similar to those observed in people with psychiatric disorders, including depression. Most rodent studies have focused on the effect of social isolation during weaning or adolescence, while its effect in adult rats has not been extensively examined. In this review, we discuss the current knowledge regarding the involvement of oxidative/nitrosative stress pathways in the prefrontal cortex and hippocampus of adult male rats exposed to CSIS, focusing on hypothalamic-pituitary-adrenocortical (HPA) axis activity, behavior parameters, antioxidative defense systems, stress signaling mediated by nuclear factor-kappa B (NF-κB), and mitochondria-related proapoptotic signaling. Although increased concentrations of corticosterone (CORT) have been shown to induce oxidative and nitrosative stress, we suggest a mechanism underlying the glucocorticoid paradox whereby a state of oxidative/nitrosative stress may exist under basal CORT levels. This review also highlights the differential susceptibility of prefrontal cortex and hippocampus to oxidative stress following CSIS and suggests a possible cellular pathway of stress tolerance that preserves the hippocampus from molecular damage and apoptosis. The differential regulation of the transcriptional factor NF-κB, and the enzymes inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) following CSIS may be one functional difference between the response of the prefrontal cortex and hippocampus, thus identifying potentially relevant targets for antidepressant treatment.